PEMBAHARUAN PERATURAN PAJAK HOTEL MELALUI UNDANG UNDANG NOMOR 28 TAHUN 2009 TENTANG PAJAK DAERAH DAN RETRIBUSI DAERAH - Hendro Saptono (Faculty of Law, Universitas Diponegoro, 2010)
Local tax can be defined as tax collected by district government. Local Income was significant contributed to the attainable of district APBD value. On behalf of that goal, the regulation reform always be done for adjusting to economic dynamic nor ignoring public justice and The economic ability of public. Hotel tax is one of the local taxes which can improve local income. Moreover, hotel tax is collect based on the profit motive business activity. There were some difference regulation between Law No. 18/1997 on Local tax and retribution as changed by Law No.34/2000 about tax reform Law No. 18/1997 on local tax and retribution Local tax which concern of hotel tax has an important role to local income, on the other hand due to collect Hotel tax, the local regulation as collection basis is necessary. So that local government should prepare local regulation about hotel tax beginning by compilethe academic draft